Formation of heavy clusters in ion-irradiated compounds. (June 2019) - Kavetskyy, T.; Liedke, M.O.; Butterling, M.; Wagner, A.; Krause-Rehberg, R.; Šauša, O.; Meshi, L.; Dahan, I.; Vacik, J.; Horak, P.; Fuks, D.; Mykytenko, N.; et al.
Abstract: Ion-irradiated U(Al, Si)3 intermetallide, as an example of compounds with significantly different atomic masses of constituting atoms, was studied by slow positron beam spectroscopy in order to clarify the nature of defects accompanying the process of the ion-induced disordering of this material. The studied compound was irradiated with different Ar + ion fluences with energy 30 keV. The formation of so-called heavy clusters (Uranium in this case) has been revealed. Such clusters affect the reliability of materials in nuclear reactors. Ion-induced creation of heavy clusters can provide important properties of similar materials. Highlights: Compounds with significantly different atomic masses of components are studied. Ion-irradiated U(Al, Si)3 intermetallide is taken as an example of such compounds. The ion-induced formation of heavy (U) clusters in these compounds is established. Slow positron beam spectroscopy is applied to reveal heavy clusters. Heavy clusters allow giving the materials new properties.